Inhibition of Human Natural Killer Cell Activity by Influenza Virions and Hemagglutinin - Mao, Huawei (American Society for Microbiology (ASM), 2010)
Natural killer (NK) cells keep viral infections under control at the early phase by directly killing infected cells. Influenza is an acute contagious respiratory viral disease transmitted from host-to-host in the first few days of infection. The evasion of host innate immune defenses including NK cells is important for its success as a viral pathogen of humans and animals. NK cells encounter influenza virus within the microenvironment of infected cells. It therefore is important to investigate the direct effects of influenza virus on NK cell activity. Recently we demonstrated that influenza virus directly infects human NK cells and induces cell apoptosis to counter their function (H. Mao, W. Tu, G. Qin, H. K. W. Law, S. F. Sia, P.-L. Chan, Y. Liu, K.-T. Lam, J. Zheng, M. Peiris, and Y.-L. Lau, J. Virol. 83:9215-9222, 2009). Here, we further demonstrated that both the intact influenza virion and free hemagglutinin protein inhibited the cytotoxicity of fresh and interleukin-2 (IL-2)-activated primary human NK cells. Hemagglutinin bound and internalized into NK cells via the sialic acids. This interaction did not decrease NKp46 expression but caused the downregulation of the ζ chain through the lysosomal pathway, which caused the decrease of NK cell cytotoxicity mediated by NKp46 and NKp30. The underlying dysregulation of the signaling pathway involved ζ chain downregulation, leading to decreased Syk and ERK activation and granule exocytosis upon target cell stimulation, finally causing reduced cytotoxicity. These findings suggest that influenza virus developed a novel strategy to evade NK cell innate immune defense that is likely to facilitate viral transmission and also contribute to virus pathogenesis.